Simulation of Fatigue Crack Growth in Friction Stir-Welded Joints of 2024-T351 Aluminum Alloy - Golestaneh, Amirreza Fahim (2008)
The present work simulates and predicts the fatigue crack growth in the friction stir welded (FSW) joint of the 2024-T351 Al alloy. The simulation is used to estimate the fatigue life of this welded joint. The study is based on finite element method (FEM) and in the framework of Fracture Analysis Code for two-dimensional (FRANC2D/L), developed by Fracture Group of Cornell University. Fatigue crack behavior through the FSW joint is investigated under Linear Elastic Fracture Mechanics (LEFM) using the Paris’ model. The work concentrated on a stable crack propagation regime, the obtained fatigue life shows good agreement with experimental and analytical results. The present work incorporates a few different types of loading which are 1) the cyclic fatigue loading for the case of R= 0.1, 2) the longitudinal tensile residual stress, 3) the crack closure concept and 4) the residual stress relaxation phenomenon. In the current work the stress intensity factor is calculated by applying displacement correlation technique, which is based on calculating the displacement field around the crack tip. The maximum circumferential tensile stress method was used to predict the fatigue crack direction. In fact FRANC2D/L does not have the capacity to consider different Paris’ constants for FSW zones and it predicts the crack propagation through the welded zones by considering the same values of Paris’ constants. This work presents a strategy to investigate the crack growth based on the corresponding Paris’ constants for each FSW zone. The numerical results are validated with the previous experimental and analytical work, which show a good agreement of 88% and 97%.